The principle of Leech's politeness in the play script Ora iso mati by Andy Sri Wahyudi - Ummaiyah, Firda; Nurhayati, Endang (Universitas Dian Nuswantoro, 2025)
This research examines the principles of politeness contained in the play script “Ora Isa Mati.” The objective of this research is to explain the application of politeness principle and violation politeness principle in a play script